CALCULATION OF NET COSTS OF BASIC POSTAL SERVICES PROVISION (Perner's Contacts, 2013)
This article deals with ways of universal postal service obligation cost assesment using existing methods as Net Avoidable Cost, Entry Pricing and Profitability Cost above all. Principially, this method is the most appropriate for determination of mentioned costs, concrete usage of this method is realized by means of methodics of its practical implementation. Contribution also works on definition of basic postal services net costs and way of their calculation on the basis of domestic branch legal norms.
Keywords: universal postal services; basic postal services; net costs